Case Report: Intervention of radiotherapy improves the prognosis of rectal squamous cell carcinoma with high PD-L1 expression and enable patients to obtain NED status - Qu, Fuyin; Xiao, Linlin; Xiao, Yuting; Gao, Chao; Wang, Xuan; Wang, Yi; Gao, Yuanhang; Wu, Fengpeng; Liu, Ming (Frontiers in Immunology, 2023)
Background: Rectal squamous cell carcinoma (RSCC) is a rare malignancy of the rectal tumor. Due to its extremely low incidence, there is still a lack of high-level treatment evidence and clinical consensus on this disease.In this article, we report a treatment process of RSCC with high PD-L1 expression. Firstly, this patient received 2 cycles of Pembrolizumab immunotherapy, but the efficacy was less sanguine. Subsequently, 4 cycles of mFOLFOX6 chemotherapy were synchronously performed on the basis of the initial regimen.Although partial remission was achieved in the lymph nodes thereafter, the changes in the primary lesions were still not significant. After that, the patient received radiotherapy, and followed by 6 cycles of PC (Albumin-binding Paclitaxel and Nedaplatin) regimen chemotherapy combined with Pembrolizumab. Eventually, the patient achieved no evidence of disease (NED) status, and no signs of recurrence or metastasis were found after 12 months of follow-up.This is the first report of a RSCC patient with high PD-L1 expression achieving a complete response. Looking back over the whole treatment process of this patient, we found that the participation of radiotherapy was the inflection point of prominent efficacy, which may provide a new idea for the selection of comprehensive treatment strategies for patients with RSCC.